2013
DOI: 10.3171/2013.3.jns122132
|View full text |Cite
|
Sign up to set email alerts
|

Seizure outcome in surgically treated drug-resistant mesial temporal lobe epilepsy based on the recent histopathological classifications

Abstract: D rug-resistant MTLE is the most common type of epilepsy requiring surgical treatment, with a favorable seizure outcome being achieved in about 60%-75% of patients. 50,51,64,82,89 Clinically, MTLE is often regarded as a relatively homogeneous syndromic entity, with seizures characterized by typical ictal semiology 32,96 and EEG findings. 29,96 However, a variety of MTLE subtypes have been described according to the underlying etiology, with different surgical prognoses. 47,89,92 Recent neuropathological classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
43
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 99 publications
(150 reference statements)
8
43
0
2
Order By: Relevance
“…26 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) 36 (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) 85 (91) 62 (67) Type 1 70 (74) 33 (47) 38 (54) 27 (39) 13 (19) 6 (3-10) (25) 7 (30) 11 (48) 5 (22) 7 ( 42 (43) 58 (60) 22 (23) 19 (20) 8 (4-13)…”
Section: (4-15)unclassified
See 1 more Smart Citation
“…26 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) 36 (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) 85 (91) 62 (67) Type 1 70 (74) 33 (47) 38 (54) 27 (39) 13 (19) 6 (3-10) (25) 7 (30) 11 (48) 5 (22) 7 ( 42 (43) 58 (60) 22 (23) 19 (20) 8 (4-13)…”
Section: (4-15)unclassified
“…[18][19][20][21] Furthermore, very few reports have considered outcomes in relation to the different HS types, and then only in the short term. 12,14,15,[22][23][24][25] The aim of this study was to investigate the relationships between the different ILAE HS types, their etiologic factors, and short-and long-term postsurgical seizure outcomes in a large cohort of HS patients undergoing surgery for drugresistant TLE because a greater understanding of the factors predicting surgical outcomes, including histopathology, may improve the selection of surgical candidates and their postsurgical clinical management.…”
mentioning
confidence: 99%
“…Postoperative outcome has been shown to be superior in patients with TLE who, after resection, were retrospectively shown to have classical patterns of HS (ie, preservation of CA2 neurons) or total HS (ie, neuronal loss throughout the CA), whereas patients with circumscribed neuronal loss of CA1 or CA4 tend to have poorer outcomes 17, 18, 19, 20. Mathern et al (1996) had previously reported that patients with initial precipitating injuries were more likely to benefit from surgery and had neuronal cell loss in CA1 and presubiculum regions.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these patterns of HS appear to be related to various clinical aspects of TLE and may have significance for postoperative prognosis. ILAE HS type 1 is more frequently associated with a history of initial precipitating injuries in early childhood, an early seizure onset and improved seizure outcome after temporal lobe surgery 17, 18, 19, 20. ILAE HS type 2 and 3 appear to be associated with a later age of onset and a less favorable postoperative outcome,17, 18, 19, 20 although there are some inconsistencies in these relationships 21.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation